2022
DOI: 10.20961/ssej.v2i2.62758
|View full text |Cite
|
Sign up to set email alerts
|

Kecanduan Smartphone dan Stres Akademik di Masa Pandemi : Sebuah Studi Potong Lintang

Abstract: <p><strong>ABSTRAK</strong></p><p><strong>Pendahuluan : </strong>Kecanduan <em>smartphone </em>merupakan perilaku terlalu lama menggunakannya tanpa melihat dampak negatif sehingga akan berpengaruh terhadap kesehatan. Kecanduan smarphone dipicu perubahan pembelajaran di masa pandemi yang mengharuskan mahasiswa banyak mengakses <em>smartphone</em>. Selain itu banyak mahasiswa yang merasakan stres karena ketidakmampuan adaptasi dengan situasi membu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In this study, it was found that the majority of children, 88 out of 114 children (77.2%), in elementary school "X" had a moderate level of smartphone addiction. Moderate smartphone addiction can be interpreted as a condition in which a person feels heavy-hearted when parting with a smartphone, even though no pathological signs have appeared yet (Sumiyarini and Yuliyani 2022). The results of this study are not in line with the research of Vyas (2021) on subjects of schoolchildren aged 8-12 years in Nadiad City, India, which stated that out of 100 children, the majority of children as many as 49 people (49%) had a severe level of smartphone addiction (Vyas 2021).…”
Section: Dimension Analysis Of Smartphone Addiction Scale (Sas)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was found that the majority of children, 88 out of 114 children (77.2%), in elementary school "X" had a moderate level of smartphone addiction. Moderate smartphone addiction can be interpreted as a condition in which a person feels heavy-hearted when parting with a smartphone, even though no pathological signs have appeared yet (Sumiyarini and Yuliyani 2022). The results of this study are not in line with the research of Vyas (2021) on subjects of schoolchildren aged 8-12 years in Nadiad City, India, which stated that out of 100 children, the majority of children as many as 49 people (49%) had a severe level of smartphone addiction (Vyas 2021).…”
Section: Dimension Analysis Of Smartphone Addiction Scale (Sas)mentioning
confidence: 99%
“…To feel the sensation of pleasure again a person will be more intense to access a smartphone. This is what causes a person to experience addiction and feel heavy to part with a smartphone (Sumiyarini and Yuliyani 2022).…”
Section: Dimension Analysis Of Smartphone Addiction Scale (Sas)mentioning
confidence: 99%
“…Smartphone is an important tool in daily life [1], because the smartphone provides several applications including information, communication, entertainment and education [2]. Another function of smartphones today can be as a tool for data collection [3], preventing psychiatric disorders, chronic diseases and to improve the quality of life in the elderly [4]. Smartphones are believed and proven to have provided many benefits and help in everyday life [5], but if the use of smartphones is done excessively [6], it can lead to smartphone addiction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Jumlah pengguna smartphone pun diprediksi semakin meningkat kedepannya. Penggunaan gadget di Indoneisa mencapai 69,4 juta orang dan diperkirakan jumlah smartphone aktif di Indonesia yang terjadi pada tahun 2018 dan 2019 akan terus bertambah menjadi 92 juta orang [7].…”
unclassified